A TRANSITIVITY ANALYSIS OF MATERIAL PROCESSES IN A CORPORATE NON-DISCLOSURE AGREEMENT: A SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE - Hendra Nugraha; Widia Yanelyn; Hilarius Raditya Priambada Purba (Universitas Lambung Mangkurat, 2025)
Language is a social semiotic resource that individuals utilize to express meanings in context and achieve their purposes. In Systemic Functional Linguistics (SFL), the transitivity system is a common means used to construe human experience into a set of process types. The present study aimed to discover the process types of transitivity system in the legal document. Data was obtained from PT. Warlbor International Indonesia, Non-Disclosure Agreement and descriptive qualitative research was used as the research method. The findings show that the material processes have the highest frequency with 47 occurrences (50%) among all the processes. The relational processes come in the second highest frequency with 31 occurrences (33%), followed by the mental processes with 14 occurrences (15%) for third place. Verbal processes, with a total of 2 occurrences or 2%, rank in the fourth position. However, neither behavioural nor existential processes are discovered in the data sources analyzed. The highest percentage of material processes usage implies that legal documents primarily describe the external world, including things, events, and human actions or about what humans have done.